Development of a primary care curriculum for medical undergraduates in Malaysia: A Delphi study / Haymond Prasad Narayanan - Haymond Prasad, Narayanan (2019)
Over the last few decades, primary care has been recognized as a cornerstone for an efficient and effective healthcare system. However, the discipline is now facing challenges like the shortage of primary care doctors, which has been attributed to the hidden curriculum of undergraduate medical programs. The aim of this project is to develop a primary care curriculum for medical undergraduates in Malaysia. A Delphi survey, which consisted of three iterative rounds with feedback, was used for this research project. The participants consisted of primary care experts who are also involved with undergraduate primary care teaching. The experts were selected based on criteria which were developed with two senior academicians in undergraduate primary care medical education. The final developed curriculum contained 34 core clinical topics and 15 core Entrustable professional activities (EPAs). The developed curriculum provides a list of core clinical topics that should be taught as part of undergraduate primary care curriculum and the expected EPAs of a new graduate on the first day of entering the primary department as a houseofficer. This work may inform policies and guidelines, and also influence undergraduate primary care education at various medical schools. This may promote and encourage more doctors to choose primary care. Furthermore, it addresses the gap in knowledge about education in primary care in Malaysia. Keywords : curriculum development, primary care, entrustable professional activities, Delphi, medical education